Sada bahar teesri jamat k lia - Ahsaan,Fouzia Farooqi (Karachi: Oxford university press, 2024)
The book includes a variety of engaging narratives that introduce students to different themes such as friendship, responsibility, and nature. Through vibrant illustrations and relatable characters, children explore their surroundings and learn important life lessons. The text is crafted to enhance vocabulary and reading skills while promoting comprehension through interactive activities.
Keywords: Sada bahar- Textbook